LANGUAGE STYLE IN STUDENTS’ SHORT STORY WORK - Dian Risdiawati; Mohammad Khadziqun Nuha (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
This study aimed to describe the style implemented based on direct and indirect meaning, namely rhetorical style and figurative language short story by high school students of class XII Brawijaya Smart School (BSS) Malang based on (1) use and (2) function. The study uses qualitative method with descriptive design. The approach used is a stylistic approach. The use of the stylistic approach in this research is to see the form of the beauty of the language used in the students' short stories. The data sources of this research are short stories by the students of class XII A2 SMA Brawijaya Smart School (BSS) Malang in the 2020/2021 academic year, as many as 15 short stories. The instruments used to collect data are worksheets/LKS, language style codification guides, and rubrics for data collection and analysis. The result of this research show that the short story of students use rhetorical style and figurative language. The rhetorical style detectable 18 type and the most is eufemismus style and the figurative language detectable 10 type and the most is metaphor style. The function of the rhetorical style is to present ideas in a more lively and interesting way, to describe the atmosphere in a more lively and interesting way, to support or refute an idea, and to convey ideas indirectly. In addition the function of figurative language style is to present ideas in a more lively and interesting way, to describe the atmosphere in a more lively and interesting way, to suppress or refute an idea, and to convey ideas indirectly.